The History of the Olympic Capital Sochi 2014: the Scientific Research Aspect - Susanna D. Bagdasaryan (Centre for Behaviour and Wellness Advocacy, 2015)
The article is devoted to the formation of the historical school for the study of the region of the city-resort of Sochi. Regional history is an integral part of the formation of the historical area of the country, dictates the internal processes of registration of statehood, imposes the specifics of the internal and external policy of the state. Sochi as an object of scientific study is the result of the efforts of the last two decades scientists Sochi State University, which raised the question of the transition from the level of regional studies, local journalistic literature to the theoretical approaches of historical analysis using the apparatus of the scientific method. The city of Sochi - the capital of Winter Olympic Games of 2014, leading to interest from foreign historical schools, researchers. This provides a historiographical analysis of the history of Sochi and makes for international studies focus on the role of regional historians, in light of the historical processes which took place on the Northern Black sea region in different periods of historical time.